ANALISIS E-LEARNING READINESS PADA PEMBELAJARAN KIMIA DI SMA NEGERI KOTA BANDA ACEH - Muammar Yulian; Chusnur Rahmi; Ade Rida Wahyuni (UIN AR-RANIRY, 2022)
The Covid-19 pandemic has changed our activities, including activities in the learning process. Previously, the learning process was carried out directly in the classroom, but the pandemic has changed into online learning such as e-learning. The implementation of e-learning in schools should be followed by an analysis of the level of e-learning readiness (ELR). This study aims to determine the readiness level of State Senior High Schools (SMA Negeri) Banda Aceh, namely SMA Negeri 1, SMA Negeri 3 and SMA Negeri 4. The method used in this study was descriptive qualitative with the number of research subjects as many as 94 students and 2 teachers in each school. The instrument used in this study was a questionnaire compiled and validated based on the Aydin & Tasci ELR model. The results showed that the three schools obtained ELR scores respectively, SMA Negeri 1 () = 3.53, SMA Negeri 3 () = 3.54. The score showed that these schools are ready but need a few improvements in applying e-learning at school. Aspects that must be improved are humans, technology, innovation, and development.